Translation and cultural adaptation of the Childbirth Experience Questionnaire (CEQ) in Iran - Zahra Abbaspoor; Lida Moghaddam-Banaem; Shabnam Ronaghi; Anna Dencker (Wolters Kluwer Medknow Publications, 2019)
Background: A standardized method to measure and quantify women's birth experiences is required to study satisfaction of childbirth care. Therefore, this study aimed to translate and culturally adapt the Childbirth Experience Questionnaire (CEQ) for use in Iran. Materials and Methods: This was a cross-sectional study including 203 women who attended 2 hospitals and 2 health centers and met the inclusion criteria in Ahvaz city, between February 2013 and June 2014. After forward and backward translation of the Swedish CEQ into Persian language, content validity was assessed by an expert panel. Scale reliability (internal consistency and test-retest reliability) was assessed with respect to the psychometric properties of the scale. Results: Minor cultural differences were identified and resolved during the translation process. One item was excluded. The intraclass correlation coefficient ranging from 0.63 to 0.90 was satisfactory. Conclusions: The Persian version of the CEQ appears to be valid and reliable; hence, it can be an effective tool in designing childbirth experience interventions and also childbirth care and education interventions for the promotion of positive childbirth experience in Iranian women.